TR4 Nuclear Receptor Different Roles in Prostate Cancer Progression - Lin, Shin-Jen; Yang, Dong-Rong; Li, Gonghui; Chang, Chawnshang (Frontiers in Endocrinology, 2015)
Nuclear receptors are important to maintain the tissue homeostasis. Each receptor is tightly controlled and under a very complicated balance. In this review, we summarize the current findings regarding the nuclear receptor TR4 and its role in prostate cancer (PCa) progression. In general, TR4 can inhibit the PCa carcinogenesis. However, when PPARγ is knocked out, activation of TR4 can have an opposite effect to promote the PCa carcinogenesis. Clinical data also indicates that higher TR4 expression is found in PCa tissues with high Gleason scores compared to those tissues with low Gleason scores. In vitro and in vivo studies show that TR4 can promote PCa progression. Mechanism dissection indicates that TR4 inhibits PCa carcinogenesis through regulating the tumor suppressor ATM to reduce DNA damages. On the other hand, in the absence of PPARγ, TR4 tends to increase the stem cell population and epithelial-mesenchymal transition (EMT) via regulating CCL2, Oct4, EZH2, and miRNA-373-3p expression that results in increased PCa carcinogenesis. In opposition to PCa initiation, TR4 can increase PCa metastasis via modulating the CCL2 signals. Finally, targeting TR4 enhances the chemotherapy and radiation therapy sensitivity in PCa. Together, these data suggest TR4 is a key player to control PCa progression and targeting TR4 with small molecules may provide us a new and better therapy to suppress PCa progression.